2021
DOI: 10.21608/ejhm.2021.207819
|View full text |Cite
|
Sign up to set email alerts
|

The Potential Protective Impact of Spirulina on Cisplatin Induced-Renal Toxicity in Adult Male Albino Rats: Histological, Immunohistochemical and Biochemical Study

Abstract: Introduction: Cisplatin (CP) is regarded as a prevalent anticancer medication utilized against several cancer types. Spirulina (SP), a blue-green alga, has been utilized as a nutritional supplementation, in addition to other therapeutic enforcement. Spirulina includes lipids, proteins, carbohydrates, and vitamins including a pigmented protein and b-carotene besides some vital minerals. Objectives: The present study was carried out to verify the toxic impacts of cisplatin on kidney of the rat and the probable p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 24 publications
1
0
0
Order By: Relevance
“…A study done by Shalan and Abd El Fattah [ 49 ] showed that cisplatin caused severe caspase-3 activity in the renal tissue especially the renal tubules which was parallel with the findings in the present work.…”
Section: Discussionsupporting
confidence: 91%
“…A study done by Shalan and Abd El Fattah [ 49 ] showed that cisplatin caused severe caspase-3 activity in the renal tissue especially the renal tubules which was parallel with the findings in the present work.…”
Section: Discussionsupporting
confidence: 91%